A Multiple Indicators and Multiple Causes Model of Alternative Tobacco Use - Nasim, Aashir (2013)
OBJECTIVE: To examine the relationship between adolescents’ cigarette smoking experiences and alternative tobacco product (ATP) use. METHODS: Multiple indicators and multiple causes (MIMIC) models estimated simultaneously the relationship between cigarette smoking experiences and ATP use among high school students (N=1827) completing the 2009 Virginia Youth Tobacco Survey. RESULTS: Overall, ATP use was associated with adolescents’ ever use of cigarettes, early onset of cigarette smoking, cigarettes smoked per day, and peer smoking; however, important model differences between racial/ethnic groups were observed. CONCLUSIONS: Prevention and cessation programs might reduce adolescent ATP use by targetting specific characterstics of cigarette smoking.